The effects of a plyometric and resistance training program on bone density in adolescent girls - Witzke, K.; Snow, S. (Medicine & Science in Sports & Exercise, 1997)
We investigated the effects of plyometric and resistance training on BMD in 14-yr old girls. Fifty-three girls completed the 9-month program. Exercisers trained 30-45 minutes, 3 times/week. Weighted vests were used for squats, lunges, calf raises, and jumping. Plyometrics included hopping, jumping, bounding, and depth jumps.The changes in all variables for the exercisers were not significantly greater than controls. Although improvement in BMD tended to be higher in the exercisers, especially for the greater trochanter (GT), these differences were not significant. The variety of lateral movement activities performed by the exercise group may have contributed to the large differences observed between groups for GT BMD and medial/lateral balance. Since the GT is a common osteoporotic fracture site, and since a majority of hip fractures occur from falls to the side (often related to strength and balance problems), resistance training involving a lateral component may have implications for fracture prevention. Future studies, however, should be longer than 9 months to determine if this intervention strategy is able to produce significant improvements in BMD, strength, and balance.